Socialization of Increasing Digital Literacy Literacy of BUMDES Administrators in Creating Independent Villages and Increasing the Welfare of MSMEs in Villages: Pengabdian - Afif Syarifudin Yahya; Eris Nur Dirman; Purwaka Hari Prihanto; Delvy Mardvin Siokain; Akbar Tanjung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Socialization of strengthening digital literacy for Village-Owned Enterprises administrators in order to create independent tourist villages and improve the welfare of MSMEs in rural areas. This socialization was carried out in a number of Bugel villages in Ciawi, Balla villages in Luwuk, and Bahar Mulya villages in Muaro Jamb. this socialization aims to improve the digital literacy of Village-Owned Enterprise administrators in creating independent tourist villages and improving the welfare of rural community MSMEs. The author believes that increasing digital literacy will increase creativity, improve the management system and promotional reach to create tourist villages that generate a lot of income and of course can increase the original village income in accordance with the objectives of establishing Village-Owned Enterprises. If the creativity and management system of Village-Owned Enterprises increase, the creation of independent tourist villages can be achieved. If an independent tourist village is achieved, the number of visitors will increase and the potential income of MSMEs will also increase. The author believes that this can improve the welfare of rural MSMEs.